(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2025)
More than is apparent in most of the existing studies, Edgard Varèse’s experience with electronic composition, is closely linked to a profound reflection on the relationship between music and film, almost as if the two artistic expressions were to be considered closely linked, almost inseparable. Déserts (1954), albeit only in intention, La procession de Verges (1955) and Poème électronque (1959) pioneeringly investigate different ways of understanding music in relation to moving images: from the fictional work to the documentary film, and to the multimedia experience. Only recently, now immersed in the digital production world of DAWs, does the new medium – as often happens – allow us to shed new light on the “old” analogue world and enable us to fully understand the visionary force of Varesi’s aesthetics and the poignancy of his way of understanding music and images. The paper retraces the compositional parabola that involved the author for the last years of his life, setting it down in the recording studios and human environments in which he found himself operating, in order to reconstruct, through the dense network of relationships between technology and thoughts, the milieu that gave rise to one of the multiple roots of film music.